Physical Transformation of Local Residences into Homestays in Gampong Nusa Aceh Besar - Suhaira, Haifa; Nareswari, Ardhya (Universitas Negeri Yogyakarta, 2025)
This research aims to enhance the potential of tourism amenities in Gampong Nusa, specifically focusing on homestays. The houses used as homestays possess significant local value and include permanent residences of individuals affected by the tsunami, which adds to their appeal as a physical attraction. Consequently, it is essential to study the physical transformation of local dwellings into homestays in Gampong Nusa, Aceh Besar. The research employs a deductive qualitative methodology, involving field observations and the collection of data on the physical transformation of homestays in Gampong Nusa, Aceh Besar through observation, documentation, and interviews with homestay managers. The study aims to describe the physical transformation process and identify the changes that occur in local dwellings when they are converted into homestays. This includes examining the transformation of residential houses at various stages: before becoming a homestay, during the transition, and after the conversion. Three types of houses are analyzed: heritage houses, residential houses, and heritage-permanent houses. The study identifies changes in space expansion, zoning, spatial elements, and functions. The most significant spatial expansion occurs in heritage houses, including the addition of three kitchen and bathroom spaces, a living room, a sleeping room, a homestay bedroom, and a warehouse. Spatial zoning transformation in heritage houses involves substantial changes in public, semi-public, and private zones, often resulting in mixed-use spaces within a single building. The addition of furniture elements is prevalent in ten houses that serve as research objects, particularly in homestay bedrooms. The spaces that have changed include bedrooms, family rooms, kitchens, and bathrooms. This study provides a detailed account of the physical transformations in residential houses converted into homestays in Gampong Nusa, Aceh Besar, contributing valuable insights into the adaptation process and its implications for tourism amenities.